Web-Based Intellectual Property (IP) Management Application For Postgraduate Student Project. - Qasim, Hussein Salem (2008)
Managing students projects takes allot of time because of increasing number of postgraduate students in UUM, It usually takes long time for manage student project. This study aims to identify, propose and develop a prototype of an online IP managing system. The proposed model is developed for CAS lecture and active postgraduate student as the user. A structured questionnaire to identify the requirement and the usually questionnaire was distributed for 20 postgraduate students and 10 lectures at CAS. The study find out that the system is accepted by the lecture and postgraduate students towards the application on aspect of including the easiness, accessibility, quality of information provided in the application management system.